The nature of the [C ii] emission in dusty star-forming galaxies from the SPT survey. Issue 3 (3rd April 2015) - Gullberg, B.; De Breuck, C.; Vieira, J. D.; Weiß, A.; Aguirre, J. E.; Aravena, M.; Béthermin, M.; Bradford, C. M.; Bothwell, M. S.; Carlstrom, J. E.; Chapman, S. C.; Fassnacht, C. D.; et al.
Abstract : We present [C ii ] observations of 20 strongly lensed dusty star-forming galaxies at 2.1 < z < 5.7 using Atacama Pathfinder EXperiment and Herschel . The sources were selected on their 1.4 mm flux ( S 1.4 mm > 20 mJy) from the South Pole Telescope (SPT) survey, with far-infrared (FIR) luminosities determined from extensive photometric data. The [C ii ] line is robustly detected in 17 sources, all but one being spectrally resolved. 11 out of 20 sources observed in [C ii ] also have low- J CO detections from Australia Telescope Compact Array. A comparison with mid- and high- J CO lines from Atacama Large Millimeter/submillimeter Array reveals consistent [C ii ] and CO velocity profiles, suggesting that there is little differential lensing between these species. The [C ii ], low- J CO and FIR data allow us to constrain the properties of the interstellar medium. We find [C ii ] to CO(1–0) luminosity ratios in the SPT sample of 5200 ± 1800, with significantly less scatter than in other samples. This line ratio can be best described by a medium of [C ii ] and CO emitting gas with a higher [C ii ] than CO excitation temperature, high CO optical depth τCO(1–0) ≫ 1, and low to moderate [C ii ] optical depth τ _[C II] ≲ 1. The geometric structure of photodissociation regions allows for such conditions.